Food security and child food poverty in Peru: Analysis for public policy design toward 2030 - Julio C. Navarro Falconi (2025)
Food security is one of the most pressing challenges of the 21st century, especially concerning children. This article analyzes the situation of food security and child food poverty at the global, regional, and national levels, with emphasis on the case of Peru. Through a review of current data, it examines the prevalence of food insecurity that affected 51 % of Peruvian households in 2021 and its evolution through 2023. The data reveal that globally, 181 million children under five years of age live in severe food poverty, while in Peru, 56.5 % of households with children under five are affected by food insecurity. The analysis identifies three key structural factors: poor food environments, inadequate feeding practices in early childhood, and low-income levels. The findings show that more than 54 % of children in severe food poverty belong to middle- or upper-class households, indicating that the problem transcends traditional economic barriers. Specific recommendations are proposed to be considered in the implementation of Peruvian public policies aligned with the 2030 Agenda, including the transformation of food systems, strengthening health systems, activating social protection mechanisms, and improving data systems to enable continuous monitoring.Keywords: Food insecurity, child poverty, early childhood.